LITERATURE STUDY OF THE RELATIONSHIP OF KNOWLEDGE AND DISEASE PERCEPTION OF MELLITUS DIABETES WITH SELF-CARING BEHAVIORS OF DIABETES MELLITUS PATIENTS - Mutmainah, Ainun; Dalle, Ambo; Askar, M (Journal of Applied Health Management and Technology, 2021)
Diabetes Mellitus is a chronic disease that requires self-care in a long or long term so that patients can perform self-care independently to prevent complications from Diabetes Mellitus. Self-care behavior aims to assess and classify the extent to which Diabetes Mellitus sufferers perform self-care in order to improve their welfare and quality of life. This study aims to determine the relationship between knowledge and pain perception about Diabetes Mellitus with the self-care behavior of Diabetes Mellitus sufferers. This research is a literature study that summarizes some of the relevant literature collected using Google Scholar published in 2015-2020. The search results showed 46 identified journals and 7 journals that met the inclusion criteria. The results showed that there was a significant relationship between knowledge of Diabetes Mellitus and the self-care behavior of Diabetes Mellitus patients and there was a significant relationship between the perception of pain about diabetes mellitus and the self-care behavior of diabetes mellitus patients.